(untitled) (Journal of Student Affairs in Africa, 2026)
In this study, we explored the potential of self-study methodology in facilitating academic advisor professional growth. Despite its extensive use in teacher education, to our knowledge, self-study is yet to be applied to academic advising. An academic advisor documented her advising experiences over a twelve-year period. Guided by the tenets of self-study, the academic advisor in collaboration with a critical friend, critically examined her experiences. The self-study methodology created space for intentional and systematic examination of the advisor’s practice, a process that has led to the emergence of innovations in her practice. These innovations included deeper engagement with students’ curricular structures, their sociocultural contexts, and individual learning habits. The advisor’s practice evolved from a generic, one-size-fits-all model to a more contextualised and relational pedagogy grounded in pedagogical content knowledge (PCK). This study highlights how intentional reflection on disorienting dilemmas and practitioner knowledge enabled the academic advisor to personalise support and foster student agency. It further illustrates the value of relationality in advising, where learning is co-constructed rather than prescribed. Ultimately, this research confirms the transformative potential of self-study in academic advisor professional development.